Modeling and simulation the transient stability analysis of the ST1A exciter model using dynamic computation for power system (DCPS) / Mohamad Hafis Nordin - Nordin, Mohamad Hafis (2009)
This paper presents a modeling and simulation of the transient stability analysis of the ST1A exciter system model by using Dynamic Computation for Power system (DCPS). This study concentrates on the transient stability analysis of power system by using an STIA exciter model. The thesis looked into the effects of using ST1A excitation system on electrical power generation system and transmission system. The thesis first explains the definition of power system stability and the need for power system stability studies. The studies also include the DCPS program. It then proceeded to discuss on the various type of excitation system. The thesis also provided a brief introduction on basic control theory and study of ST1A exciter model. Next the thesis discusses how to linerized the ST1A exciter block diagram. This thesis was using an Euler's method to design a program of STIA exciter model. The discussions was given for each block of the exciter. The program of DCPS was used as a main of the simulation program. The thesis then performed a power system modeling and simulation of six bus test power systems. The fault was injected into the system and exciter parameters were varied to test the transient stability of the power system and the effectiveness of the STIA as an exciter in six bus test system. Examples of the parameters that were varied include the fault position, the clearing time and the all the parameter of the exciter. Lastly, a conclusion was made on the overall effect of STIA exciter on the power system and the transient stability of the power system when its parameters were varied.